2008
DOI: 10.1039/b804836c
|View full text |Cite
|
Sign up to set email alerts
|

Liver autofluorescence properties in animal model under altered nutritional conditions

Abstract: Autofluorescence spectroscopy is a promising and powerful approach for an in vivo, real time characterization of liver functional properties. In this work, preliminary results on the dependence of liver autofluorescence parameters on the nutritional status are reported, with particular attention to vitamin A and lipid accumulation in liver tissue. Normally fed and 24 h starving rats were used as animal models. Histochemical and autofluorescence analysis showed that lipids and vitamin A colocalize in the liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 36 publications
6
16
0
Order By: Relevance
“…A good correlation is found between AF of vitamin A and NRfluorochromized lipids as to both fluorescence intensity and spatial distribution. These results are in agreement with previous findings on the direct relationship between localization and amount of vitamin A and lipids, in the parenchima of a rat model of liver lipid accumulation induced by acute starvation [24].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A good correlation is found between AF of vitamin A and NRfluorochromized lipids as to both fluorescence intensity and spatial distribution. These results are in agreement with previous findings on the direct relationship between localization and amount of vitamin A and lipids, in the parenchima of a rat model of liver lipid accumulation induced by acute starvation [24].…”
Section: Discussionsupporting
confidence: 83%
“…Vitamin A detection: performed by means of Gold chloride (GC) staining procedure [31], modified as already described [24]. Briefly Lipid detection: performed by means of Nile Red (NR) (Eastman Kodak Co., Rochester, NY) fluorochromization [32].…”
Section: Histochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, it is to take into account that only a part of lipids can give rise to a noticeable AF emission, obviously depending on lipid molecular features. Preliminary indications demonstrated that marked AF signals and photolability are exhibited by fatty acids such as arachidonic, linoleic, and stearic acids, while other derivatives such as butirric and palmitic acids, triglycerides, and phospholipids are in general poorly fluorescent ([22, 24, 47] and unpublished results). Further and complex studies would be however required to define more precisely the AF properties of the numerous lipid derivatives.…”
Section: Discussionmentioning
confidence: 94%
“…The fixed tissue was embedded in paraplast and processed for light microscopy. 10 Non-viable cells were identified by trypan blue nuclear staining, in tissue sections stained with eosin or hematoxylin/eosin (E/E).…”
Section: Methodsmentioning
confidence: 99%